2019
DOI: 10.31223/osf.io/nmwkx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the statistical significance of foreshock sequences in Southern California

Abstract: Earthquake foreshocks may provide information that is critical to short-term earthquake forecasting. However, foreshocks are far from ubiquitously observed, which makes the interpretation of ongoing seismic sequences problematic. Based on a statistical analysis, Trugman and Ross (2019, https:// doi.org/10.1029/2019GL083725) suggested that as much as 72% of all mainshocks in Southern California is preceded by foreshock sequences. In this study, we reassess the analysis of Trugman and Ross (2019, https://doi.org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The analysis of an highly complete earthquake catalog in Southern California showed that 72% of M W ≥ 4 earthquakes in the region are preceded by an elevated seismic activity compared with the background seismicity rate (Trugman & Ross, 2019), suggesting that foreshock activity is more ubiquitous than previously thought. However, a recent reanalysis of the same catalog suggested that a much smaller portion of these foreshock sequences were really anomalous and could not be attributed to temporal fluctuations in background seismicity rate (van den Ende & Ampuero, 2020). Although anomalous foreshock sequences currently appear to be the exceptional, the improvement of near‐fault geodetic and seismological observational capabilities are essential to bridge the gap between natural fault observations and laboratory experiments, where foreshocks are commonly observed.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of an highly complete earthquake catalog in Southern California showed that 72% of M W ≥ 4 earthquakes in the region are preceded by an elevated seismic activity compared with the background seismicity rate (Trugman & Ross, 2019), suggesting that foreshock activity is more ubiquitous than previously thought. However, a recent reanalysis of the same catalog suggested that a much smaller portion of these foreshock sequences were really anomalous and could not be attributed to temporal fluctuations in background seismicity rate (van den Ende & Ampuero, 2020). Although anomalous foreshock sequences currently appear to be the exceptional, the improvement of near‐fault geodetic and seismological observational capabilities are essential to bridge the gap between natural fault observations and laboratory experiments, where foreshocks are commonly observed.…”
Section: Discussionmentioning
confidence: 99%
“…Foreshock patterns in nature can be challenging to identify due to sparseness in seismicity and/or a lack of network coverage (Bakun et al., 2005 ). However, there are well documented examples of increased foreshock activity prior to the mainshock (Bouchon et al., 2013 ; Brodsky & Lay, 2014 ; Ellsworth & Bulut, 2018 ; Gulia & Wiemer, 2019 ; Gulia et al., 2016 ; Kato et al., 2016 ; Nanjo et al., 2012 ; Papadopoulos et al., 2010 ; Trugman & Ross, 2019 ; van den Ende & Ampuero, 2020 ; Wyss & Lee, 1973 ; Yoon et al., 2019 ). In some cases, the Gutenberg‐Richter b ‐value decreases prior to the mainshock (Gulia et al., 2016 ; Nanjo et al., 2012 ); implying that foreshock magnitude increases systematically as the fault approaches failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, this can lead to misguided conclusions about how foreshock patterns evolve in space and time. For instance, Trugman and Ross ( 2019 ) implemented a template matching approach (Quake‐Template‐Matching or QTM) and demonstrated that foreshock sequences may be more common than previously thought (see also van den Ende & Ampuero, 2020 ). This observation was driven by the fact that the QTM catalog was able to lower the magnitude of completeness well below that of standard catalogs.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that detailed earthquake detections could bear important information about an impending earthquake. The seismic activity observed in the 20‐day window before M ≥ 4 earthquakes was later re‐evaluated by van den Ende and Ampuero (2020, V&A from here on) to investigate in which cases these increases in seismicity were significant compared to the natural fluctuations of the seismicity rate. In their approach, V&A choose to test seismic activities smoothed at 20 days against a model that accounts for increases in seismicity.…”
Section: Introductionmentioning
confidence: 99%